Amaranth protein films reinforced with maize starch nanocrystals - Condes, María Cecilia (2015)
The effect of the addition of starch nanocrystals e prepared from waxy and normal maize starch granules e to amaranth protein formulations on the physicochemical and structural properties of the resulting nanocomposite films was studied. All nanocomposites films were homogeneous, translucent and had similar thickness and optical properties than the neat protein film due to the good dispersion of the nanoreinforcements in the protein matrix and the good chemical affinity between both components. Nevertheless, the presence of nanocrystals affected differently the way in which protein matrix stabilized, according to the origin of the reinforcement: mainly by disulfide bonds for waxy maize nanocrystals and by hydrogen bonds for normal maize nanocrystals. This induced a different reinforcing effect for amaranth protein films, being more significant for normal maize nanocrystals that however presented a lower crystallinity. Moreover, nanocomposite films presented improved water vapor permeability (WVP), water uptake (WU), surface hydrophobicity and mechanical behavior than proteins films and also a delay in their weight loss in soil.